Iron Deficiency, a Risk Factor of Thyroid Disorders in Reproductive-Age and Pregnant Women: A Systematic Review and Meta-Analysis - Luo, Jingyi; Wang, Xiaoxia; Yuan, Li; Guo, Lixin (Frontiers in Endocrinology, 2021)
Background: Iron deficiency (ID) is concerned as the most common nutritional deficiency worldwide. The effects of ID on thyroid function and autoimmunity in pregnant women and reproductive-age women are controversial. The aim of the current study was to summarize the evidences and evaluate the relationship between ID and thyroid disorders. Methods: In this systematic review and meta-analysis, Studies published on the Cochrane, Embase, Medline and PubMed databases by October 2020 were searched. 636 studies discussed the correlation between ID and thyroid disorders were eligible in the initial search. Pooled mean differences (MD) and 95% confidence intervals (CI) were calculated for the assessment of thyrotropin (TSH) and free thyroxine (FT4) levels. Combined odd ratios (OR) and 95% CI were calculated for the assessment of the prevalence of overt and subclinical hypothyroidism, positive thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). Results: For women of reproductive age, ID could significantly increase the risk of positive TPOAb (OR: 1.89; 95% CI: 1.17, 3.06: P = 0.01) and both positive TPOAb and TgAb (OR: 1.48; 95% CI: 1.03, 2.11: P = 0.03). The meta-analysis of pregnant women showed that pregnant women with ID had increased serum TSH levels (MD: 0.12; 95% CI: 0.07, 0.17; P < 0.00001) and decreased FT4 levels (MD: -0.73; 95% CI: -1.04, -0.41; P < 0.00001). Meanwhile, the prevalence of overt (OR: 1.60; 95% CI: 1.17, 2.19; P = 0.004) and subclinical (OR: 1.37; 95% CI: 1.13, 1.66; P = 0.001) hypothyroidism in pregnant women with ID was significantly increased. Conclusions: ID may adversely affect thyroid function and autoimmunity of pregnant and reproductive-age women and it is very necessary for monitoring iron nutritional status and early treatment of ID for them.